Falsafat Metafisika : Tela’ah Filosuf Iqbal dan Pemikirannya - Fathullah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2020)
This paper understands that the falsafah metaphysic Iqbaland him intelligention is concepted to self, khudi. Apply for that concept to intelligent. Iqbal is filosuf and Islamytheolog. Him thingking about all of in the world back to being reality is god, human beings and world. But good reality is absolut. Iqbal ‘s concept on the universe cannot be separated from his concept of god dan human beings. The universe should be understood as an organism which always grows without the end. Igbal’s aims at changing the face of Islam become an action religion that stresses the progress and dynamic so that there would be reconstruction of the Islamic concepts.